TREN PENGETAHUAN SIKAP DAN PERILAKU (PSP) REMAJA TERHADAP ISU KEPENDUDUKAN - Anastasia Septya Titisari (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2018)
Adolescents are group of population that contributte in demographic bonus. This occurs when the number ofproductive ages is greater than the nonproductive. If not managed properly, demographic bonuses will result innegative effects to development. Therefore, adolescents should be equipped with useful sciences. One of them isconcerning population. Besides providing an understanding of population control, the goal is also to provide anunderstanding the maturing age of marriage. This is related to fulfilling the rights of health and reproduction foradolescents. This study discusses about knowledge, attitude, and behaviour trend of adolescents (15-24 years old)towards population seen from RPJMN Survey data (2007-2015). The result shows that adolescent knowledge aboutfertile period and pregnancy is still fluctuating. As for methods of contraceptive knowledge and the willingness touse contraceptive in the future having an increasing trend. The RPJMN survey shows most adolescents know properage of marriage and having children. The survey data trend also shows that adolescent attitudes tends to maturethe age of marriage, to plan the number of children, and to control the birth space. There is also an increase in thepercentage of adolescents who become increasingly concerned about population issues by knowing the effects ofpopulation growth and realizing the importance of government programs in regulating population growth..